Pengaruh Komunikasi, Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Karwikarya Wisman Graha Tanjugpinang - Dayu Fatira; Lia Suprihartini; Dodi Dermawan (Bahtera Inovasi, 2018)
This study entitled "The Effect of Communication, Compensation, and Work Discipline on Employee Performance at PT. Karwikarya Graha Tanjungpinang Wisman. This study uses a quantitative method with data collection techniques through distributing questionnaires, library data, and references to previous journals. The sample in this study were employees in the production section of PT. Karwikarya Wisman Graha Tanjungpinang totaling 115 employees with sampling techniques from a population of 162 employees using the Slovin formula. While the data analysis uses Multiple Linear Regression analysis using SPSS 22. From the results of the Multiple Linear Regression test it can be seen that the Adjusted R Square value is 0.940 or 94.0%. So that it can be explained that 94.0% of Communication, Compensation and Work Discipline Variables affect employee performance. while the rest (100% -94.0% = 6%) is influenced by other variables not discussed in this study. The results of this study conclude that: (1) Partial communication does not have a positive effect on employee performance, (2) Partial Compensation has a positive effect on employee performance, (3) Work Discipline Partially has a positive effect on employee performance. Meanwhile, based on the results of the simultaneous test found that communication, compensation, and work discipline together on the performance of employees at PT. Karwikarya Wisman Graha Tanjungpinang.